Proceedings of the 2023 International Conference on Wireless Communications, Networking and Applications - Siarry, Patrick; Jabbar, M. A.; Cheung, Simon King Sing.; Li, Xiaolong; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2025)
This open access book includes original, peer-reviewed research papers from the 2023 International Conference on Wireless Communications, Networking and Applications (WCNA 2023), held in Shenzhen, Guangdong, China, from December 29 to 31, 2023. The topics covered include but are not limited to: Wireless Communications; Devices, Tools, and Techniques for WSN and Other Wireless Networks; Wireless Sensor Networks; Internet of Things (IoT); AI; Signal Processing; and Sustainable Pervasive WSN Applications. The papers showcased here share the latest findings on Wireless Communications, Networking and Applications, making the book a valuable asset for researchers, scientists, scholars, engineers and students from the universities all around the world and the industry.
Wireless Communications -- Devices, Tools, and Techniques for WSN and other wireless networks -- Wireless Sensor Networks -- Sustainable Pervasive WSN Applications.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Telecommunication; Electronics; Signal processing; Computational intelligence; Communications Engineering, Networks; Electronics and Microelectronics, Instrumentation; Signal, Speech and Image Processing; Computational Intelligence